Soft Selling as an Influencer Marketing Communication Strategy in Shaping Gen-Z's Consumer Behavior - Yusni Rahma; Tengku Walisyah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The development of digital communication technology has transformed marketing communication practices, particularly through social media platforms that enable influencers to become strategic actors in delivering promotional messages. One widely implemented approach is soft selling, where promotional content is presented subtly through lifestyle representation, personal narratives, and authentic experiences. Previous studies have largely examined influencer marketing from the perspective of purchase intention, brand awareness, and consumer engagement, while limited attention has been given to how soft selling communication strategies construct lifestyle meanings and gradually shape consumptive tendencies among Generation Z. This study aims to analyze how influencers implement soft selling strategies and how these strategies influence the formation of Gen Z consumer behavior. Using a descriptive qualitative approach, data were collected through interviews with five Gen Z informants aged 18–28 years and content analysis of influencer accounts on Instagram and TikTok. The findings reveal that soft selling strategies operate through impression management, consistent personal branding, and identity commodification, causing products to be perceived as part of an aspirational lifestyle. The novelty of this research lies in explaining soft selling not only as a marketing technique but also as a symbolic communication process that shapes consumption meanings. Theoretically, this study contributes to influencer marketing and communication studies by emphasizing the relationship between digital identity construction, lifestyle representation, and consumer behavior formation.